Farmer Preparedness and Constraints for Agribusiness Opportunities at Vizhinjam International Seaport, Kerala - Jestas, Jils; K.G. Sangeetha,; S Anupma, (Indian Journal of Extension Education, 2025)
The study was conducted during 2024-25 in Thiruvananthapuram district, Kerala, to assess farmer preparedness and constraints in leveraging agribusiness opportunities associated with the Vizhinjam International Seaport. The principal objective was to identify and prioritize constraints affecting farmer participation in port-led agribusiness. A total of 100 farmers were selected using purposive and random sampling techniques. Data were collected through a structured interview schedule, focus group discussions, and expert consultations. The Garrett Ranking Technique was applied to rank the identified constraints. The results revealed that institutional and policy barriers such as frequent policy shifts and inadequate extension–export support were ranked as the most severe. Market fragmentation, weak farmer collectives, land fragmentation, labour scarcity, and digital gaps also limited preparedness. Farm-level and compliance-related challenges, including stagnant productivity and certification costs, were reported but considered relatively less critical. It was concluded that systemic and governance issues outweigh farm-level problems in determining export readiness. The study highlights the need for policy stability, farmer-centric export schemes, strengthened FPOs, ICT-enabled extension, and targeted capacity building to ensure inclusive integration of smallholders into global value chains through Vizhinjam Seaport.